A solid-phase regeneration method of retired lithium iron phosphate positive electrode material
Patent Information
- Application Number
- CN202611238224.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]然而,现有技术中,退役磷酸铁锂电池的放电处理与正极材料再生往往被设置为各自独立的工序,从而未能有效利用电池残余电量;正极片中聚偏氟乙烯粘结剂及有机残留物的去除与铝箔集流体的分离亦存在效率低、引入杂质多或产生废液等问题;补锂与碳层重构的协同工艺参数尚待优化
[0028]本发明的一种退役磷酸铁锂正极材料的固相再生方法,将退役磷酸铁锂电池的残余电量利用、正极片还原焙烧预处理与固相再生工艺有机衔接,利用残余电量驱动外置碱性水电解单元制氢,实现了退役电池的安全放电和氢气的原位供给;采用含氢还原气氛热处理结合机械剥离,避免了强碱溶铝带来的废液问题和杂质引入;通过锂源、碳源与分段式固相烧结的配合,同步实现了补锂、晶格修复和导电碳层重构;本发明工艺流程短,杂质引入少,无需废液处置,环境友好,能够在保留磷酸铁锂橄榄石晶体结构的基础上恢复其电化学性能,尤其适用于退役磷酸铁锂电池正极材料的大规模直接再生利用。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of resource utilization technology for spent lithium-ion batteries, specifically to a solid-phase regeneration method for retired lithium iron phosphate cathode materials. Background Technology
[0002] Lithium iron phosphate (LFP) batteries have been widely used in power batteries and energy storage batteries due to their advantages such as high safety, long cycle life, and low cost. However, as early LFP batteries used in vehicles and energy storage are gradually retired, the issue of resource utilization of spent LFP batteries is becoming increasingly prominent.
[0003] Existing methods for recycling spent lithium-ion batteries mainly include pyrometallurgical recycling, hydrometallurgical recycling, and direct regeneration. Pyrometallurgical recycling typically requires high-temperature processing, resulting in high energy consumption and potentially damaging the original crystal structure of the cathode material. While hydrometallurgical recycling offers higher metal recovery rates, it is a lengthy process, consumes significant amounts of acid and alkali reagents, and generates wastewater treatment issues. For lithium iron phosphate materials, which do not contain high-value metals such as nickel and cobalt, the economic and environmental benefits of using traditional pyrometallurgical or hydrometallurgical methods are limited.
[0004] After long-term cycling, the main causes of failure in lithium iron phosphate cathode materials include loss of active lithium, increase in lattice defects, damage to the surface carbon layer, and encapsulation by impurities such as binders, electrolytes, and reaction products with the cathode material. If the lithium source can be replenished and structural defects repaired without destroying its olivine crystal framework, the cathode material can be directly regenerated.
[0005] However, in the existing technology, the discharge treatment of retired lithium iron phosphate batteries and the regeneration of cathode materials are often set as separate processes, thus failing to effectively utilize the residual power of the batteries; the removal of polyvinylidene fluoride binder and organic residues in the cathode sheet and the separation of aluminum foil current collectors also have problems such as low efficiency, introduction of many impurities or generation of waste liquid; the synergistic process parameters of lithium replenishment and carbon layer reconstruction need to be optimized.
[0006] Therefore, developing a direct regeneration method for retired lithium iron phosphate cathode materials that has a shorter process, lower energy consumption, and can preserve the material structure and restore electrochemical performance is of great application value in this field. Summary of the Invention
[0007] Based on the above background, the purpose of this invention is to provide a solid-phase regeneration method for retired lithium iron phosphate cathode materials, thereby realizing the resource utilization of residual power in retired lithium iron phosphate batteries, efficient pretreatment of cathode sheets, and structural repair and electrochemical performance restoration of lithium iron phosphate materials.
[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0009] A solid-phase regeneration method for retired lithium iron phosphate cathode materials, comprising the following steps:
[0010] After waterproofing the casing of the retired lithium iron phosphate battery, the positive and negative terminals are exposed and placed in an alkaline water electrolysis unit. The residual charge of the retired lithium iron phosphate battery drives the alkaline water electrolysis unit to perform electrolysis. The generated gas is collected, and the hydrogen in it is separated and dried before being sent to a reduction roasting device.
[0011] Disassemble the discharged retired lithium iron phosphate battery to obtain a positive electrode sheet; place the positive electrode sheet in the reduction calcination apparatus, and heat-treat the positive electrode sheet at a temperature of 500℃~650℃ for 10~60min in a reducing atmosphere in which the hydrogen gas fraction is 1~5% and the balance is an inert gas.
[0012] The heat-treated positive electrode sheet is mechanically peeled, ground, and sieved to obtain pretreated lithium iron phosphate positive electrode powder.
[0013] The pretreated lithium iron phosphate cathode powder is mixed with a lithium source and a carbon source to obtain a regenerated precursor mixture;
[0014] The regenerated precursor mixture was subjected to segmented solid-state sintering under an inert protective atmosphere. First, a first sintering was performed at 300℃~400℃ and held for 1~3 hours, followed by a second sintering at 600℃~700℃ and held for 8~16 hours to obtain the regenerated lithium iron phosphate cathode material.
[0015] The residual charge of retired lithium iron phosphate (LFP) batteries drives an external alkaline water electrolysis unit, which converts the residual electrical energy stored in the battery into the chemical energy of hydrogen, enabling safe discharge and energy recovery of retired batteries. This avoids the energy waste caused by traditional resistance discharge or short-circuit discharge, and provides an in-situ hydrogen source for subsequent reduction and calcination of the cathode sheet. Heat treatment of the cathode sheet at 500℃~650℃ for 10~60 minutes in a reducing atmosphere with 1%~5% hydrogen gas and the remainder being inert gas achieves thermal decomposition of the polyvinylidene fluoride (PVDF) binder and effective removal of organic residues, while avoiding abnormal growth of LFP particles or damage to the olivine structure caused by prolonged high temperatures. After mixing the pretreated LFP cathode powder with lithium and carbon sources, segmented solid-state sintering is performed. This promotes uniform contact and initial reaction between the lithium source and the LFP particle surface at low temperatures, and achieves deep diffusion of lithium ions into lithium-depleted regions and repair of lattice defects at high temperatures. Simultaneously, the carbon source pyrolysis forms a conductive carbon layer, thus simultaneously completing lithium replenishment, lattice reconstruction, and conductive network rebuilding.
[0016] Preferably, the electrolyte in the alkaline water electrolysis unit is a potassium hydroxide aqueous solution with a concentration of 1 mol / L to 5 mol / L. The retired lithium iron phosphate battery is placed in front of the alkaline water electrolysis unit, and any leaks in the casing of the retired lithium iron phosphate battery are sealed with waterproofing material.
[0017] Preferably, the hydrogen in the gas is stored in a hydrogen buffer container after gas separation and drying, and is mixed with the inert gas before being introduced into the reduction roasting device; one or more of the following components are provided between the hydrogen buffer container and the reduction roasting device: a check valve component, a flame arrestor component, a pressure regulating component, and a gas flow control component.
[0018] Preferably, the inert gas is argon, the volume fraction of hydrogen in the reducing atmosphere is 5%, and the positive electrode is heat-treated at 600°C for 30 minutes.
[0019] These optimized parameters ensure that the polyvinylidene fluoride binder is fully decomposed while preserving the olivine crystal structure of lithium iron phosphate to the greatest extent, thus avoiding local agglomeration and abnormal growth caused by prolonged high temperatures.
[0020] Preferably, the heat-treated positive electrode sheet is mechanically peeled, ground, and sieved, specifically including: after cooling the heat-treated positive electrode sheet, separating the lithium iron phosphate positive electrode active material from the aluminum foil current collector by mechanical peeling, and grinding and sieving the lithium iron phosphate positive electrode active material obtained by peeling.
[0021] Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide, and lithium acetate, and the carbon source is one or more of glucose, sucrose, and citric acid; the amount of lithium source added is determined based on the amount of lithium missing from the pretreated lithium iron phosphate cathode powder relative to its stoichiometric composition.
[0022] Preferably, the carbon source is glucose, and the amount of glucose added is 10wt% to 25wt% of the mass of the pretreated lithium iron phosphate cathode powder.
[0023] This addition range can form a suitable carbon coating layer on the surface of lithium iron phosphate particles, ensuring the reconstruction of the conductive network while avoiding excessive carbon source that leads to a decrease in crystallinity.
[0024] Preferably, the inert protective atmosphere is nitrogen, argon, or a mixture of nitrogen and argon; the first sintering is carried out at 350°C and held for 2 hours, followed by a second sintering at 650°C and held for 12 hours.
[0025] This preferred sintering method can form a uniform reaction interface at low temperatures and achieve sufficient lattice repair at high temperatures, resulting in regenerated lithium iron phosphate materials with high crystallinity and excellent electrochemical performance.
[0026] Preferably, the exhaust gas outlet of the reduction roasting device is connected to an exhaust gas purification unit, which includes one or more of a dust removal component, an alkali absorption component, and an adsorption component.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] This invention discloses a solid-phase regeneration method for retired lithium iron phosphate (LFP) cathode materials. It organically integrates the utilization of residual charge from retired LFP batteries, cathode sheet reduction and calcination pretreatment, and solid-phase regeneration processes. The residual charge drives an external alkaline water electrolysis unit to produce hydrogen, achieving safe discharge of retired batteries and in-situ hydrogen supply. The method employs heat treatment in a hydrogen-containing reducing atmosphere combined with mechanical stripping, avoiding waste liquid problems and impurity introduction caused by strong alkali aluminum dissolution. Through the coordination of lithium and carbon sources with segmented solid-phase sintering, lithium replenishment, lattice repair, and conductive carbon layer reconstruction are simultaneously achieved. This invention features a short process flow, minimal impurity introduction, no waste liquid disposal required, and is environmentally friendly. It can restore the electrochemical performance of LFP batteries while preserving their olivine crystal structure, making it particularly suitable for large-scale direct regeneration of retired LFP battery cathode materials. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0030] Figure 1 This is a schematic diagram of the process flow for the direct regeneration method of cathode material of retired lithium iron phosphate batteries provided in an embodiment of the present invention;
[0031] Figure 2 This is a schematic diagram of the waterproof sealing of a retired lithium iron phosphate battery provided in an embodiment of the present invention;
[0032] Figure 3 This is a schematic diagram of a discharge processing flow based on water electrolysis provided in an embodiment of the present invention;
[0033] Figure 4 These are X-ray diffraction patterns of pretreated products from different pretreatment methods provided in embodiments of the present invention;
[0034] Figure 5 These are scanning electron microscope images of the cathode material obtained from mechanical disassembly;
[0035] Figure 6This is a scanning electron microscope image of the cathode material obtained after calcination at 600°C for 4 hours, provided in an embodiment of the present invention.
[0036] Figure 7 This is a scanning electron microscope image of the cathode material obtained after calcination at 600°C for 30 minutes, provided in an embodiment of the present invention.
[0037] Figure 8 This is a scanning electron microscope image of the positive electrode material obtained by immersion in sodium hydroxide according to an embodiment of the present invention;
[0038] Figure 9 These are X-ray diffraction patterns of lithium iron phosphate samples repaired with different formulations according to embodiments of the present invention;
[0039] Figure 10 These are gas curves generated during sample restoration under different pretreatment conditions provided in embodiments of the present invention.
[0040] Figure 11 These are X-ray diffraction patterns of lithium iron phosphate samples repaired using different pretreatment methods provided in embodiments of the present invention.
[0041] Figure 12 These are scanning electron microscope images of lithium iron phosphate samples repaired using different pretreatment methods provided in embodiments of the present invention.
[0042] Figure 13 These are cyclic voltammograms of lithium iron phosphate batteries repaired using different pretreatment methods provided in embodiments of the present invention.
[0043] Figure 14 These are electrochemical impedance spectroscopy curves of lithium iron phosphate batteries repaired under different pretreatment methods provided in the embodiments of the present invention.
[0044] Figure 15 The embodiments of the present invention provide different pretreatment methods for the repaired low-frequency region Z of lithium iron phosphate samples. re With ω -1 / 2 Relationship diagram;
[0045] Figure 16 These are rate performance diagrams of lithium iron phosphate batteries repaired using different pretreatment methods provided in embodiments of the present invention.
[0046] Figure 17 These are the first charge-discharge performance, cycle performance, and charge-discharge curves of lithium iron phosphate batteries repaired with different pretreatment methods provided in the embodiments of the present invention. Detailed Implementation
[0047] The technical solution of the present invention will be further described in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any modifications and / or alterations made to the present invention will fall within the protection scope of the present invention.
[0048] In this invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art. Unless otherwise specified, the components or equipment in the following embodiments are general standard parts or components known to those skilled in the art, and their structures and principles can be learned by those skilled in the art through technical manuals or conventional experimental methods.
[0049] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings. In this detailed description, numerous specific details are set forth to facilitate explanation and provide a thorough understanding of the embodiments of the present invention. However, one or more embodiments may be practiced by those skilled in the art without these specific details.
[0050] like Figure 1 As shown, an embodiment of the present invention provides a solid-phase regeneration method for retired lithium iron phosphate cathode materials. This method first performs a retired battery discharge treatment step S1. A retired 18650 type lithium iron phosphate battery is selected as the experimental subject, as follows... Figure 2 As shown, the positive electrode of the battery is first sealed with silicone rubber spraying. A 1 mol / L potassium hydroxide aqueous solution is prepared as the electrolyte for the alkaline water electrolysis unit. The residual charge of the retired lithium iron phosphate battery drives the alkaline water electrolysis unit for electrolysis. The discharge time is 48 hours, and the gases generated during the discharge process are collected, such as... Figure 3 As shown.
[0051] After collecting the generated gas, the hydrogen undergoes gas separation and drying to remove entrained oxygen, electrolyte droplets, and water vapor. The treated hydrogen is stored in a hydrogen buffer container and then mixed with argon to form a reducing atmosphere with a hydrogen component of 5% and the remainder being argon, which is then introduced into the reduction roasting apparatus. A check valve, flame arrestor, pressure regulating component, and gas flow control component are installed between the hydrogen buffer container and the reduction roasting apparatus to ensure the safe and stable delivery of hydrogen.
[0052] Step S2 involves disassembling the discharged lithium iron phosphate battery to obtain the positive electrode sheet. The positive electrode sheet is cut into 2cm × 2cm pieces, placed in a quartz boat, and then placed in the tube furnace reaction zone (reduction calcination apparatus) for heat treatment step S3. A mixture of hydrogen and argon is introduced as the reducing atmosphere, with a gas flow rate controlled at 200mL / min. The temperature is increased to 600℃ at a rate of 10℃ / min and held for 30min. During the heating and holding process, the polyvinylidene fluoride binder undergoes thermal decomposition, conductive carbon black and electrolyte residues are gradually removed, and the positive electrode material separates from the aluminum foil current collector. After the holding period, the battery is allowed to cool naturally to room temperature.
[0053] After heat treatment, the positive electrode sheet is cooled, and the lithium iron phosphate positive electrode active material is mechanically peeled off from the surface of the aluminum foil current collector using a scraper. It is then sieved using a 200-mesh sieve to obtain pretreated lithium iron phosphate positive electrode powder.
[0054] In step S4, the pretreated lithium iron phosphate cathode powder is mixed with lithium carbonate and glucose to obtain a regenerated precursor mixture. Specifically, the amount of lithium carbonate added is 10 at.% to compensate for the theoretical lithium defect in the pretreated lithium iron phosphate cathode powder, based on elemental lithium content; the amount of glucose added is 15 wt% of the mass of the pretreated lithium iron phosphate cathode powder. The above materials are mixed evenly to obtain a uniformly mixed regenerated precursor.
[0055] The regenerated precursor mixture was placed in a quartz boat and subjected to a segmented solid-state sintering step S5 under a nitrogen protective atmosphere. In the first stage, the temperature was raised to 350℃ and held for 2 hours to provide a uniform and stable interfacial reaction basis for subsequent high-temperature lattice repair. Under this temperature condition, the lithium source and carbon source formed a relatively uniform reaction interface on the particle surface. Driven by the concentration gradient, lithium ions initially diffused and penetrated into the lithium-depleted region on the surface of the lithium iron phosphate material, forming a locally lithium-rich interface on the particle surface, providing favorable conditions for subsequent lithium ion diffusion and lattice repair under high-temperature conditions. In the second stage, the temperature was further raised to 650℃ and held for 12 hours. The high-temperature conditions significantly improved the diffusion capacity of lithium ions, causing the added lithium source to gradually migrate to the lithium-depleted region and promoting the repair of antisite defects and local lattice distortions in lithium iron phosphate. As sintering continued for a long time, the lithium concentration gradient inside the material gradually decreased, and the crystal structure tended to be stable and uniform. Simultaneously, glucose pyrolysis formed a uniform conductive carbon layer coating the surface of the lithium iron phosphate particles. After sintering, the material was cooled to room temperature in the furnace to obtain the regenerated lithium iron phosphate cathode material.
[0056] To verify the impact of different pretreatment times in step S3 on the regeneration effect, a comparative experiment was conducted. The holding time at 600℃ in step S3 was adjusted to 4 hours, while the remaining steps remained the same as in the previous embodiment. The results showed that both holding at 600℃ for 4 hours and holding at 600℃ for 30 minutes could achieve complete removal of polyvinylidene fluoride (PVDF). However, online monitoring of the flue gas revealed that various volatile gases were mainly released during the heating stage and the initial holding period, and after holding at 600℃ for 30 minutes, virtually no new gaseous products were generated. Therefore, extending the holding time did not further improve the impurity removal effect but instead increased energy consumption. This demonstrates the superiority of using 600℃ for 30 minutes as the preferred pretreatment condition in the embodiments of this invention.
[0057] To verify the impact of different pretreatment methods in step S3 on the regeneration effect, another comparative experiment was conducted. The pretreatment method in step S3 was adjusted to soaking in sodium hydroxide solution, while the remaining steps were the same as in the aforementioned embodiments. Specifically, the cut positive electrode sheet was soaked in a 10wt% sodium hydroxide solution for 15 minutes. After the aluminum foil was completely dissolved, it was filtered and repeatedly washed with deionized water until the pH of the filtrate was less than 7.5. Then, it was dried in a vacuum drying oven at 80°C for 12 hours. The resulting positive electrode material was subjected to lithium replenishment in step S4 and sintering repair in step S5 according to the method in the aforementioned embodiments. The results showed that sodium hydroxide treatment can achieve separation of the positive electrode material from the aluminum foil, but due to the complexity of the washing process, there are waste liquid treatment problems, and it is easy to introduce impurity ions. In comparison, the high-temperature short-time pretreatment process used in the embodiments of the present invention is simpler to operate and has better industrial adaptability.
[0058] like Figure 4 As shown, X-ray diffraction was used to analyze the phase composition of different products with different pretreatment times and methods. The results showed that the diffraction peaks of the pretreated products were consistent with the standard structure card of lithium iron phosphate olivine, and no obvious impurity phases were detected. Simultaneously, analysis of the X-ray diffraction pattern of the untreated sample (labeled S-LFP-Md in the figure) revealed a certain degree of graphitized carbon phase, which may originate from conductive agents or carbon residues in the electrode. No obvious impurity peaks were found in the other three pretreated groups, indicating that pretreatment removed the graphitized carbon crystals on the surface of the cathode material, providing favorable conditions for subsequent cathode material repair.
[0059] like Figure 5-8As shown, the morphology of each material was observed using a scanning electron microscope. Whether processed for 4 hours or 30 minutes, the original amorphous coating layer in the images had largely disappeared, and the lithium iron phosphate particles became more clearly defined with relatively clean surfaces, exhibiting a looser particle aggregation state. A short calcination of 30 minutes was sufficient to expose most of the particles. High-temperature reduction calcination effectively decomposes or pyrolyzes impurities such as polyvinylidene fluoride binder, conductive carbon network, and residual electrolyte coating on the surface of the lithium iron phosphate particles. The volatilization and decomposition of organic matter removes impurities that cause particle agglomeration, thus successfully dispersing the aggregated lithium iron phosphate particles. Samples treated with sodium hydroxide immersion are shown below. Figure 8 As shown, the morphology of the samples treated with sodium hydroxide solution immersion differs from that of the reduction-calcined samples. Although some lithium iron phosphate particles are visible, large clumps are observed in both high- and low-magnification images, indicating that the particles still exhibit agglomeration. The main purpose of sodium hydroxide solution immersion is to dissolve the aluminum foil current collector through strong alkaline corrosion. However, due to the extremely strong chemical stability and alkali resistance of the polyvinylidene fluoride binder, the sodium hydroxide solution cannot destroy the polyvinylidene fluoride and conductive agent network inside the particles. This indicates that simple alkaline immersion cannot achieve effective separation of the cathode material and the organic binder.
[0060] like Figure 9 As shown, the diffraction peak positions of all repair samples using different formulations in step S4 basically match the characteristic peaks of the standard card at the bottom, indicating that the lithium iron phosphate structure of the waste material was effectively restored after solid-state sintering repair. However, there are significant differences in the diffraction peak intensities of samples with different formulations, indicating that the crystallinity is greatly affected by the formulation, and some samples have impurity peaks, indicating the introduction of other impurities. When the glucose addition amount increases to 25 wt%, the X-ray diffraction peak intensity of the samples decreases significantly, and the baseline fluctuation of some samples increases. Excess glucose generates a thick amorphous carbon layer during high-temperature carbonization. This carbon layer covers the surface of lithium iron phosphate particles, which to some extent hinders the contact diffusion between particles and grain growth, thereby limiting the further growth of lithium iron phosphate crystals and leading to a decrease in the crystallinity of the material. The presence of amorphous carbon also causes an enhancement of the X-ray diffraction background signal and a rise in the baseline, further indicating an increase in the amorphous carbon content in the samples. Therefore, a glucose addition amount of 15 wt% is more conducive to maintaining the crystal structure of the material.
[0061] With a fixed glucose addition of 15 wt%, comparing samples with different lithium source additions, the sample with a 10 at.% lithium carbonate and 15 wt% glucose ratio exhibited the sharpest diffraction peaks, the highest peak intensity, and the flattest background baseline, showing the highest agreement between its diffraction characteristics and the standard card. In contrast, the sample with a 5 at.% lithium carbonate and 15 wt% glucose ratio showed slightly weaker peak intensity and obvious impurity peaks at 2θ=22.25°, 2θ=23.1°, and 2θ=24.7°, which, upon analysis, showed better agreement with the lithium phosphate standard card. This phenomenon indicates that during the remediation of waste lithium iron phosphate, a 5 at.% lithium source provides an excessive amount of lithium ions, resulting in the formation of lithium phosphate impurities, which may affect subsequent electrochemical performance. A 10 at.% lithium compensation amount can more accurately fill lithium vacancies generated during long-term cycling, thereby effectively eliminating lattice defects, promoting lattice reconstruction, and obtaining lithium iron phosphate materials with high crystallinity and a pure phase.
[0062] like Figure 10 As shown, the gas generation patterns of different pretreatment times and methods exhibit high consistency and all show obvious bimodal characteristics. In the inert atmosphere, the large amount of released carbon monoxide gas plays a crucial role in gas-phase reduction. Compared with the limitations of direct contact reduction with solid carbon, gaseous carbon monoxide has extremely strong permeability, allowing it to penetrate deep into the pores of lithium iron phosphate particles, extract lattice oxygen from ferric oxide, precisely reduce ferric iron to ferrous iron, and, together with lithium ions in the system, reintegrate into the lattice, completing the crystal repair and electrochemical activity restoration of the olivine phase of lithium iron phosphate. The concentrated release of methane indicates that glucose is transforming into amorphous carbon, and also proves that a conductive carbon network forms on the surface of the regenerated lithium iron phosphate particles in an oxygen-free environment. This uniform carbon coating layer can inhibit the abnormal growth of lithium iron phosphate grains under high-temperature repair, which is also an important reason for the excellent high-rate performance recovery after material repair.
[0063] like Figure 11As shown, X-ray diffraction analysis was performed on three groups of lithium iron phosphate samples repaired using different pretreatment times and methods. From the overall diffraction peak positions, the X-ray diffraction patterns of the repaired samples, regardless of whether they underwent alkaline washing with sodium hydroxide solution or heat treatment at 600℃, corresponded to the standard cards at the bottom. No obvious peaks of common impurities such as ferric oxide and lithium triphosphate were observed in the patterns, indicating that all three pretreatment methods, combined with the subsequent solid-state sintering process, effectively promoted the regeneration of waste lithium iron phosphate and the appearance of the target phase. However, the overall intensity of the diffraction peaks in the sodium hydroxide chemically pretreated samples was relatively weak, and the peak shape was slightly broadened. This suggests that the sodium hydroxide chemical pretreatment may not have completely removed impurities from the surface of the waste material, such as residual binders or electrolyte byproducts, or that the alkaline washing process caused some damage to the original structure of the material, resulting in incomplete grain development during subsequent high-temperature sintering and relatively poor crystallinity of the repaired material. In contrast, the two samples pretreated at 600℃ showed higher intensity X-ray diffraction peaks, a flat background baseline, and a high signal-to-noise ratio. This indicates that the reduction roasting method can more effectively decompose impurities such as organic binders and conductive agents on waste electrodes, providing a purer environment for subsequent lithium compensation and lattice reconstruction, thereby greatly promoting the growth and crystallization of lithium iron phosphate crystals. Furthermore, comparing two samples treated at 600℃ for 30 min and 4 h, their X-ray diffraction patterns showed high consistency in peak intensity and position, with no significant differences. This suggests that a reduction roasting time of 30 min is sufficient to remove the main impurities affecting the repair process.
[0064] like Figure 12 As shown in the figure, scanning electron microscopy was used to characterize three groups of lithium iron phosphate samples after regeneration using different pretreatment times and methods. Group (a) consists of samples calcined at 600℃ for 4 hours, group (b) consists of samples calcined at 600℃ for 30 minutes, and group (c) consists of samples calcined by immersion in sodium hydroxide solution. The samples calcined at 600℃ for 30 minutes exhibited suitable grain size and excellent conductive network, further confirming from a microscopic perspective that 600℃ for 30 minutes is the optimal pretreatment condition for direct solid-phase regeneration of waste lithium iron phosphate.
[0065] Cyclic voltammetry tests were performed on three groups of lithium iron phosphate samples that had been repaired using different pretreatment times and methods. Figure 13Cyclic voltammetry curves of these three samples at a scan rate of 0.001 V / s are shown. As can be seen from the figure, all samples exhibit the typical characteristics of lithium iron phosphate materials, namely, the presence of a distinct pair of oxidation and reduction peaks. This corresponds to the redox reaction between ferrous and ferric iron during lithium-ion intercalation and deintercalation during charge and discharge. Among them, the sample subjected to reduction roasting at 600℃ for 30 min showed the smallest potential difference between the oxidation and reduction peaks at 0.268 V, exhibiting the best electrochemical reversibility. Simultaneously, its redox peaks were the sharpest and most symmetrical, and it also possessed the highest peak current. The higher peak current indicates that a greater proportion of the active material participated in the electrochemical reaction at the same potential scan rate, reflecting the material's faster charge transfer rate and excellent lithium-ion diffusion capability.
[0066] like Figure 14 As shown, electrochemical impedance spectroscopy (EIS) tests were performed on three groups of lithium iron phosphate samples repaired using different pretreatment times and methods. The impedance spectra of all samples consisted of a semicircle in the high-to-mid-frequency region and a diagonal line in the low-frequency region. The diameter of the semicircle in the high-frequency region represents the charge transfer resistance at the material-electrolyte interface, while the diagonal line in the low-frequency region corresponds to the Weber impedance of lithium ion diffusion within the active material particles. In the mid-frequency region, the sample subjected to reduction calcination at 600℃ for 30 min exhibited the smallest semicircle diameter, indicating that this sample had the smallest charge transfer resistance. This demonstrates that direct repair after appropriate high-temperature pretreatment effectively restored the lattice defects on the material surface, optimized the solid-liquid interface, and facilitated electron exchange and ion transport at the interface.
[0067] Data in the low-frequency region can be used to further quantify the diffusion capacity of lithium ions. Lithium-ion diffusion coefficient ( The square of the Weber factor (σ) is inversely proportional to the square of the Weber factor (σ). According to the formula... In this study, linear fitting was performed on the low-frequency data, and the results are as follows: Figure 15 As shown, the slope k value of the reduction-calcined sample held at 600℃ for 30 min was the smallest, indicating that the lithium-ion diffusion coefficient inside the material was the largest.
[0068] like Figure 16As shown, multi-gradient rate performance tests were conducted on three groups of lithium iron phosphate samples repaired using different pretreatment times and methods. The test current density was increased progressively in the order of 0.1C, 0.2C, 0.5C, 1C, and 2C, and then returned to 0.1C, with 7 cycles at each rate. When the test current density suddenly dropped from 2C back to 0.1C, the capacity of all three samples could quickly recover to a level basically consistent with the initial 0.1C stage. In particular, the sample calcined at 600℃ for 30 min showed a rapid and stable capacity recovery to nearly 148 mAh / g, with an extremely high capacity recovery rate. This excellent capacity recovery ability proves that the regenerated material has excellent electrochemical reversibility, indicating that after experiencing a severe high-current impact, the crystal structure of the material remains intact and stable, without irreversible structural damage.
[0069] like Figure 17 As shown, detailed charge-discharge tests were conducted on three groups of lithium iron phosphate samples repaired using different pretreatment times and methods. The figure shows the first-cycle charge-discharge specific capacity and initial coulombic efficiency of each sample at a low rate of 0.1C. The sample calcined at 600℃ for 30 min exhibited the best initial electrochemical performance, with first-cycle charge and discharge specific capacities reaching 151.09 mAh / g and 140.68 mAh / g, respectively, and the highest initial coulombic efficiency of 93.11%. The figure also shows the 100-cycle long-term cycling test for each sample, further verifying the material's stability. The sample calcined at 600℃ for 30 min consistently maintained the best performance, with its 1C discharge specific capacity remaining stable at around 130 mAh / g. After 100 cycles, the capacity showed almost no significant decay, demonstrating excellent cycle stability. The figure also shows the charge-discharge voltage curves of each sample at 1C rate for the 10th and 100th cycles. The curves of the 10th and 100th cycles of the reduction-calcined sample held at 600℃ for 30 min almost completely overlap, and the voltage difference between the charge-discharge plateaus did not increase significantly after 100 long cycles.
[0070] Based on the above test data, this embodiment further verifies the technical effectiveness of the present invention. The residual charge drives an external alkaline water electrolysis unit to produce hydrogen, which not only achieves safe discharge of the retired battery but also provides an in-situ hydrogen source for subsequent reduction roasting. The reduction roasting conditions of 600℃ for 30 minutes achieve the optimal balance between the complete decomposition of polyvinylidene fluoride and the preservation of the lithium iron phosphate structure. Mechanical stripping avoids the generation of strongly alkaline waste liquid. The ratio of 10 at.% lithium carbonate to 15 wt% glucose achieves synergistic optimization of lithium replenishment, lattice repair, and conductive carbon layer reconstruction. The segmented sintering regimes of 350℃ / 2h and 650℃ / 12h promote uniform diffusion of lithium ions and thorough repair of lattice defects. The combination of these features enables the recycled lithium iron phosphate material obtained by the method of the present invention to recover to near-new material levels in terms of crystal structure, morphological characteristics, and electrochemical performance.
[0071] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
Claims
1. A solid-phase regeneration method for retired lithium iron phosphate cathode materials, characterized in that: The method includes the following steps: After waterproofing the casing of the retired lithium iron phosphate battery, the positive and negative terminals are exposed and placed in an alkaline water electrolysis unit. The residual charge of the retired lithium iron phosphate battery drives the alkaline water electrolysis unit to perform electrolysis. The generated gas is collected, and the hydrogen in it is separated and dried before being sent to a reduction roasting device. Disassemble the discharged retired lithium iron phosphate battery to obtain a positive electrode sheet; place the positive electrode sheet in the reduction calcination apparatus, and heat-treat the positive electrode sheet at a temperature of 500℃~650℃ for 10~60min in a reducing atmosphere in which the hydrogen gas fraction is 1~5% and the balance is an inert gas. The heat-treated positive electrode sheet is mechanically peeled, ground, and sieved to obtain pretreated lithium iron phosphate positive electrode powder. The pretreated lithium iron phosphate cathode powder is mixed with a lithium source and a carbon source to obtain a regenerated precursor mixture; The regenerated precursor mixture was subjected to segmented solid-state sintering under an inert protective atmosphere. First, a first sintering was performed at 300℃~400℃ and held for 1~3 hours, followed by a second sintering at 600℃~700℃ and held for 8~16 hours to obtain the regenerated lithium iron phosphate cathode material.
2. The solid-phase regeneration method for decommissioned lithium iron phosphate cathode materials according to claim 1, characterized in that: The electrolyte in the alkaline water electrolysis unit is an aqueous solution of potassium hydroxide with a concentration of 1 mol / L to 5 mol / L.
3. The solid-phase regeneration method for decommissioned lithium iron phosphate cathode materials according to claim 1, characterized in that: The hydrogen in the gas is stored in a hydrogen buffer container after gas separation and drying, and is mixed with the inert gas before being introduced into the reduction roasting device; one or more of the following components are provided between the hydrogen buffer container and the reduction roasting device: a check valve component, a flame arrestor component, a pressure regulating component, and a gas flow control component.
4. The solid-phase regeneration method for decommissioned lithium iron phosphate cathode materials according to claim 1, characterized in that: The inert gas is argon, the volume fraction of hydrogen in the reducing atmosphere is 5%, and the positive electrode is heat-treated at 600°C for 30 minutes.
5. A solid-phase regeneration method for decommissioned lithium iron phosphate cathode materials according to claim 1, characterized in that: The process of mechanically peeling, grinding, and sieving the heat-treated positive electrode sheet includes: cooling the heat-treated positive electrode sheet, separating the lithium iron phosphate positive electrode active material from the aluminum foil current collector by mechanical peeling, and grinding and sieving the lithium iron phosphate positive electrode active material obtained by peeling.
6. A solid-phase regeneration method for decommissioned lithium iron phosphate cathode materials according to claim 1, characterized in that: The lithium source is one or more of lithium carbonate, lithium hydroxide, and lithium acetate, and the carbon source is one or more of glucose, sucrose, and citric acid; the amount of lithium source added is determined based on the amount of lithium missing from the pretreated lithium iron phosphate cathode powder relative to its stoichiometric composition.
7. A solid-phase regeneration method for decommissioned lithium iron phosphate cathode materials according to claim 6, characterized in that: The carbon source is glucose, and the amount of glucose added is 10wt%~25wt% of the mass of the pretreated lithium iron phosphate cathode powder.
8. A solid-phase regeneration method for decommissioned lithium iron phosphate cathode materials according to claim 1, characterized in that: The inert protective atmosphere is nitrogen, argon, or a mixture of nitrogen and argon; the first sintering is carried out at 350°C and held for 2 hours, followed by the second sintering at 650°C and held for 12 hours.
9. A solid-phase regeneration method for decommissioned lithium iron phosphate cathode materials according to claim 1, characterized in that: The tail gas outlet of the reduction roasting device is connected to a tail gas purification unit, which includes one or more of a dust removal component, an alkaline solution absorption component, and an adsorption component.